The Influence of Digital Literacy and Product Innovation on the Competitive Advantage of Modern Beverage Businesses - Oktavianti, Eka Putri; Jocelin, Amelia; Alghozi, Muhammad Azmie; Pramesti, Chaerunisa Cahya; Putri, Sylvia Octa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This research explores the geopolitical dynamics of the Shanghai Cooperation Organization (SCO), paying particular attention to the slogan “Central Asia for Central Asians.” Although SCO officials espouse a message of sovereignty, non-interference, and regional ownership, the investigation reveals a rift between these norms and residual patterns of China and Russia. 1) Regarding the research methodology and materials, (broadly defined at the beginning of the paper by Kaplan as a primary concern of geopolitical dynamics—sources of power) the qualitative approach and analysis of policy documents help us understand how regional independence is used both as a tool of legitimacy by Central Asian states and as a means to maintain some semblance of stability (or lack thereof) by major powers aligned with their regional interests2) On the other hand, China uses it as a tool for economic integration through the Belt and Road Initiative, and Russia uses it to maintain its elite security and business networks. Therefore, this study fills a gap in the literature by investigating the differences between institutional rhetoric and power practices within regional organizations, as well as providing a deeper understanding of Central Asia’s limited regional autonomy. The current findings also have implications for regional governance, suggesting that external dependence continues to be a determining factor in the region’s long-term policy space and sovereignty.